Optimizing Foundations: The Case for Slab Selection in Multi-Story Residential Buildings: Mengoptimalkan Pondasi: Kasus Pemilihan Pelat pada Bangunan Tempat Tinggal Bertingkat - Nargul, Saktaganova; Saken, Uderbayev; Akmaral, Zhapakhova; Gulnaz, Zhakapbayeva; Gulaina, Aben; Alina, Yespenbetova (Indonesian Journal of Innovation Studies, 2024)
This study investigates the optimal foundation design for multi-story residential buildings through a comparative analysis of two foundation variants under specific geological conditions. Employing the finite element method via SCAD software, we assessed the structural integrity and load-bearing capacities of the foundation options. Material consumption was quantified for each variant, and the consistency of settling calculations for the slab foundation was evaluated. The results indicated that the slab foundation not only minimizes material usage but also simplifies design complexity according to normative standards. Based on technical and economic assessments, the slab foundation is recommended as the most cost-effective and structurally efficient option for such construction projects. This research provides a pivotal foundation design perspective that could influence future architectural and engineering practices in residential building construction. Highlights: SCAD software validates foundation integrity via finite element analysis. Slab foundations offer superior cost and material efficiency. Simplifies design, enhancing construction process efficiency. Keywords: Structural Integrity, Slab Foundation, Reinforcement, Monolith, Building